Strategic Control And Foresight: Risk Identification And Monitoring As Levers Of Project Performance In Embu County, Kenya - Kitsao, Brian; Boniface Wambua Mbuvi; Ajai Prakash (Cita konsultindo, 2026)
The purpose of this study was to evaluate how risk identification affected construction project performance and how risk monitoring affected construction project performance in Embu County, Kenya. A sample of 288 construction project professionals was used. Descriptive design was used. Findings from correlation analysis show that risk identification had a significant and a positive correlation on construction projects’ performance (r=0.798, p= 0.001<0.05), as well as risk monitoring (r=0.798, p= 0.001<0.05). Regression analysis indicated a statistically significant predictive impact on construction projects’ performance of Embu County - Risk monitoring (β = 0.389, p=0.000 < 0.05); Risk Identification (β = 0.243in Embu County, p= 0.0001 < 0.05). The Study recommended that as a risk monitoring strategy, project teams in Embu County should create digital dashboards and perform regular evaluations for monitoring risks which emerge during the projects’ lifespan. The study contributes to the strategic management and project risk literatures by empirically demonstrating the importance of risk identification and risk monitoring as dynamic capabilities of business environments that influence construction projects performance in developing environment. In contrast to earlier research, which tended to treat the issue of risk management in generic and broad forms, the study decomposes risk management process and gives a clear statistical indication of the variable effect of particular risk management strategies. Moreover, it provides a geographically specific knowledge and situates its findings on a unique context of Embu County thereby filling the gap between international theories of risk management and local realities of a project in the sub-Saharan Africa.